A medical graphite coating and preparation method thereof
Through non-equilibrium magnetron sputtering technology, a medical graphite coating with good wetting and low cytotoxicity was prepared, which solved the problem of poor wetting of existing coatings in medical applications and achieved improvements in the biocompatibility and process efficiency of the coating.
Patent Information
- Application Number
- CN202411150329.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-21
AI Technical Summary
Graphite-like coatings prepared by existing non-equilibrium magnetron sputtering technology have poor wetting in medical applications.
By performing two unequilibrium magnetron sputtering on the carbon target and the titanium target, a transition layer and a medical graphite coating were formed respectively, and the power and gas flow of the target were adjusted to improve the wettability and biocompatibility of the coating.
The prepared medical graphite coating has good wetting and low cytotoxicity, and is suitable for protective coatings of medical devices. It has a simple process, fast deposition speed and low pollution.
Smart Images

Figure CN119040822B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a medical graphite coating and a preparation method thereof. Background Art
[0002] Magnetron sputtering is a surface treatment technology for surface modification. It introduces a magnetic field between the two poles of an electric field. Under the action of the magnetic field, electrons spiral and oscillate up and down near the target, increasing the probability of collision with charged particles and gas molecules, thereby increasing ion density and energy and achieving high-speed sputtering.
[0003] Unbalanced closed-field magnetron sputtering uses magnets with opposite adjacent poles and different strengths between the core and the outer ring to form closed magnetic lines of force. Electrons can only move between the coating area and the target material, preventing the overflow of electrons and increasing the collision probability between the plasma and the secondary electrons. The plasma is not bound around the target material, which increases the ion concentration in the coating area and improves the sputtering efficiency. Unbalanced closed-field magnetron sputtering technology greatly makes up for the shortcomings of traditional magnetron sputtering technology. Its high-efficiency ion sputtering deposition improves the quality of the coating and improves the density and roughness of the coating structure. Moreover, the ion bombardment of unbalanced magnetron sputtering can clean the impurities of the substrate, activate the surface, and help improve the bonding strength of the coating. At present, unbalanced magnetron sputtering technology is the most mainstream method for preparing graphite-like coatings.
[0004] However, the graphite-like coating prepared by unbalanced magnetron sputtering technology still has certain limitations during use, and has poor wettability when used in the medical field. Summary of the invention
[0005] The object of the present invention is to provide a medical graphite coating and a preparation method thereof. The medical graphite coating prepared by the present invention has good wettability and low cytotoxicity.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a medical graphite coating, comprising the following steps:
[0008] Performing first unbalanced magnetron sputtering on the carbon target and the titanium target respectively to form a transition layer on the surface of the substrate;
[0009] Performing a second unbalanced magnetron sputtering on the carbon target and the titanium target to form a medical graphite coating on the surface of the transition layer;
[0010] During the second unbalanced magnetron sputtering, the power of the carbon target is 4 kW and the current is 6.7 A; the power of the titanium target is 0~ 0.4kW, current 0~1.52A .
[0011] Preferably, during the first unbalanced magnetron sputtering: the initial power of the titanium target is 3kW, the initial power of the carbon target is 0.1kW, and after sputtering for 840s with the initial power of the titanium target and the initial power of the carbon target, the power of the titanium target is reduced; while reducing the power of the titanium target, the power of the carbon target is increased.
[0012] Preferably, the lowering speed is 3-10 kW / h; the raising speed is 3-10 kW / h; the lowering and raising time is 500-3000 s;
[0013] The first unbalanced magnetron sputtering ends with the completion of the lowering and the raising.
[0014] Preferably, during the first unbalanced magnetron sputtering, the flow rate of the inert gas is 25 to 40 sccm, and the vacuum degree is less than 2×10 -5 mBar, substrate bias is -60~-80V.
[0015] Preferably, during the second unbalanced magnetron sputtering, the flow rate of the inert gas is 25 to 40 sccm, and the vacuum degree is less than 2×10 -5 mBar, substrate bias is -60~-80V, and deposition time is 5400~10800s.
[0016] Preferably, during the first unbalanced magnetron sputtering and the second unbalanced magnetron sputtering, the substrate is in a rotating state, and the rotation speed of the substrate is 2-8 rpm.
[0017] Preferably, before the first unbalanced magnetron sputtering, the substrate is cleaned; the cleaning comprises: immersing the substrate in acetone and ethanol successively for ultrasonic treatment, and then performing ion bombardment.
[0018] Preferably, the frequency of the ultrasound is independently 80-120 W; and the time is independently 10-20 min.
[0019] Preferably, during the ion bombardment, the rotation speed of the substrate is 2 to 8 rpm, and the vacuum degree is less than 2×10 -5 mBar, the flow rate of inert gas is 25~40sccm, and the DC bias is -400~-500V.
[0020] The present invention also provides a medical graphite coating prepared by the preparation method described in the above technical solution.
[0021] The present invention provides a method for preparing a medical graphite coating, comprising the following steps:
[0022] Performing first unbalanced magnetron sputtering on the carbon target and the titanium target respectively to form a transition layer on the surface of the substrate;
[0023] Performing a second unbalanced magnetron sputtering on the carbon target and the titanium target to form a medical graphite coating on the surface of the transition layer;
[0024] During the second unbalanced magnetron sputtering, the power of the carbon target is 4 kW, and the current is 6.7 A; the power of the titanium target is 0-0.4 kW, and the current is 0-1.52 A.
[0025] The present invention prepares a medical graphite coating with good mechanical properties and biological properties by adjusting the power of the carbon target and the titanium target. 2 / sp 3 The content makes the connectivity of the internal structure of the coating moderate, and comprehensively optimizes the hardness, elastic modulus, friction coefficient and wear resistance of the coating; and the cytotoxicity of the coating meets the safety standards of biomedicine, because magnetron sputtering technology can effectively prevent the incorporation of toxic elements.
[0026] Compared with the traditional process, the present invention adopts an unbalanced magnetron sputtering system to prepare a titanium-doped medical graphite coating, which reduces the complexity of the process and improves the biological properties of the coating. The coating can be used as a protective coating for medical devices. The preparation method has the advantages of simple process, fast deposition speed, and low pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the medical graphite-like coating whose substrate is single crystal silicon (100) obtained in Example 1;
[0028] Figure 2 This is a SEM image of the medical graphite-like coating whose substrate is single crystal silicon (100) obtained in Example 2;
[0029] Figure 3 This is a SEM image of the medical graphite coating with a single crystal silicon (100) substrate obtained in Example 3;
[0030] Figure 4 This is a SEM image of the medical graphite-like coating whose substrate is single crystal silicon (100) obtained in Example 4;
[0031] Figure 5 This is a SEM image of the medical graphite-like coating whose substrate is single crystal silicon (100) obtained in Example 5;
[0032] Figure 6 The Raman images of the medical graphite-like coatings obtained in Examples 1 to 5 with the substrate being single crystal silicon (100);
[0033] Figure 7 The ID / IG and G peak position diagrams of the medical graphite coatings with a single crystal silicon (100) substrate obtained in Examples 1 to 5;
[0034] Figure 8The microhardness and elastic modulus diagram of the medical graphite coating obtained in Examples 1 to 5 on a medical stainless steel substrate;
[0035] Fig. 9 The friction coefficient curve of the medical graphite coating obtained in Examples 1 to 5 whose substrate is a medical stainless steel substrate;
[0036] Fig.10 The Raman images of the wear spots of the medical graphite-like coating obtained in Examples 1 to 5 whose substrate is a medical stainless steel substrate;
[0037] Fig.11 The ID / IG and G peak position diagrams of the wear spots of the medical graphite-like coating obtained in Examples 1 to 5 whose substrate is a medical stainless steel substrate;
[0038] Fig.12 is the wear rate of the medical graphite coating of Examples 1 to 5 whose substrate is a medical stainless steel substrate;
[0039] Fig.13 The contact angle of the medical graphite coating obtained in Examples 1 to 5 whose substrate is a medical stainless steel substrate;
[0040] Fig.14 The potentiodynamic polarization curves of the medical graphite-like coatings obtained in Examples 1 to 5 whose substrates are medical stainless steel substrates. DETAILED DESCRIPTION
[0041] The present invention provides a method for preparing a medical graphite coating, comprising the following steps:
[0042] Performing first unbalanced magnetron sputtering on the carbon target and the titanium target respectively to form a transition layer on the surface of the substrate;
[0043] Performing a second unbalanced magnetron sputtering on the carbon target and the titanium target to form a medical graphite coating on the surface of the transition layer;
[0044] During the second unbalanced magnetron sputtering, the power of the carbon target is 4 kW, and the current is 6.7 A; the power of the titanium target is 0-0.4 kW, and the current is 0-1.52 A.
[0045] The present invention performs first unbalanced magnetron sputtering on a carbon target and a titanium target respectively to form a transition layer on the surface of a substrate.
[0046] In the present invention, the substrate preferably comprises single crystal silicon (100) and / or a medical stainless steel substrate.
[0047] In the present invention, before the first unbalanced magnetron sputtering, preferably the substrate is cleaned; the cleaning preferably includes: immersing the substrate in acetone and ethanol successively for ultrasonic treatment, and then ion bombardment.
[0048] In the present invention, the power of the ultrasound is preferably independently 80 to 120 W, more preferably 90 to 100 W; the time is preferably independently 10 to 20 min, more preferably 12 to 13 min.
[0049] In the present invention, during the ion bombardment, the rotation speed of the substrate is preferably 2 to 8 rpm, more preferably 4 to 6 rpm, and the vacuum degree is preferably less than 2×10 -5 mBar, the flow rate of the inert gas is preferably 25 to 40 sccm, more preferably 30 to 35 sccm, the power of the carbon target is preferably 0.05 kW, the power of the titanium target is preferably 0.07 kW, and the DC bias is preferably -400 to -500 V, more preferably -450 to -480 V. Cleaning the substrate is beneficial to the adhesion of the coating.
[0050] In the present invention, during the first unbalanced magnetron sputtering: the initial power of the titanium target is preferably 3kW, the initial power of the carbon target is preferably 0.1kW, and after sputtering for 840s with the initial power of the titanium target and the initial power of the carbon target, the power of the titanium target is reduced; while reducing the power of the titanium target, the power of the carbon target is increased.
[0051] In the present invention, the speed of the reduction is preferably 3-10 kW / h, more preferably 4-8 kW / h, and further preferably 5-6 kW / h; the speed of the increase is preferably 3-10 kW / h, more preferably 4-8 kW / h, and further preferably 5-6 kW / h; the time of the reduction and increase is preferably 500-3000 s, more preferably 1000-2500 s, and further preferably 1500-1800 s; the first unbalanced magnetron sputtering is preferably terminated with the end of the reduction and increase. Setting the power gradient change is conducive to the improvement of the bonding force.
[0052] In the present invention, during the first unbalanced magnetron sputtering, the flow rate of the inert gas is preferably 25 to 40 sccm, more preferably 30 to 35 sccm, and the vacuum degree is preferably less than 2×10 -5 mBar, the substrate bias is preferably -60 to -80V, more preferably -70 to -75V.
[0053] During the first unbalanced magnetron sputtering, the substrate is preferably in a rotating state, and the rotation speed is preferably 2 to 8 rpm, more preferably 4 to 6 rpm. The rotation is to make the deposited coating more uniform, and the target material is symmetrically placed around the cavity. If it is not rotated, more target material components that are close to each other will be deposited on the sample.
[0054] In the present invention, the thickness of the transition layer is preferably 200 to 600 nm.
[0055] After forming the transition layer on the surface of the substrate, the present invention performs a second unbalanced magnetron sputtering on the carbon target and the titanium target to form a medical graphite coating on the surface of the transition layer.
[0056] In the present invention, during the second unbalanced magnetron sputtering, the flow rate of the inert gas is preferably 25 to 40 sccm, more preferably 30 to 35 sccm, and the vacuum degree is preferably less than 2×10 -5 mBar, the substrate bias is preferably -60 to -80 V, more preferably -70 to -75 V, the deposition time is preferably 5400 to 10800 s, more preferably 6000 to 10000 s, and further preferably 7000 to 9600 s. The power of the carbon target is 4 kW, and the current is 6.7 A; the power of the titanium target is 0 to 0.4 kW, more preferably 0.1 to 0.3 kW; the current is 0 to 1.52 A, more preferably 0.34 to 1.15 A, and further preferably 0.73 A.
[0057] In the present invention, during the second unbalanced magnetron sputtering, the substrate is preferably in a rotating state, and the rotation speed is preferably 2 to 8 rpm, and more preferably 4 to 6 rpm.
[0058] In the present invention, the thickness of the medical graphite coating is preferably 600-820 nm.
[0059] The present invention also provides a medical graphite coating prepared by the preparation method described in the above technical solution.
[0060] The medical graphite coating and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] Preparation, characterization and measurement instruments used in the embodiments of the present invention:
[0062] The titanium-doped medical graphite coatings obtained in the various embodiments of the present invention are all deposited and prepared using a CF-800 unbalanced closed-field magnetron sputtering ion plating system designed and produced by the British TEER Company;
[0063] The microstructure and thickness of the titanium-doped medical graphite coating were analyzed using a JSM-IT500HR scanning electron microscope (SEM) from JEOL Ltd.
[0064] The LabRAM HREvolution laser Raman spectrometer produced by HORIBA was used to analyze the molecular structure of titanium-doped medical graphite coatings.
[0065] The hardness and elastic modulus of titanium-doped medical graphite coatings were measured using a HysitronTI 980 nanoindenter produced by BRUKER.
[0066] The friction and wear coefficient of titanium-doped medical graphite coating was measured using the MFT-5000 friction and wear tester produced by Rtec, USA;
[0067] The contact angle of titanium-doped medical graphite coating was measured using a JC2000C1 contact angle meter produced by Shanghai Zhongchen Digital Technology Equipment Co., Ltd.
[0068] The equipment used in the cytotoxicity test mainly includes: CO2 constant temperature incubator (Beijing Sangyi Experimental Instrument Research Institute, model: WIGGENSWCI-180); ultra-clean workbench (Shanghai Dute Scientific Instrument Co., Ltd., model: SW-CJ-2FD); centrifuge (Shanghai Luxiangyi Centrifuge Instrument Co., Ltd., model: TD5);
[0069] Microplate reader (TECAN, model: SPARK 10M).
[0070] Example 1
[0071] (1) The single crystal silicon (100) and the medical stainless steel substrate were placed in beakers containing 100 mL of acetone and anhydrous ethanol, respectively, and ultrasonically cleaned for 20 min, respectively, with the power set to 100 W;
[0072] (2) Then, the substrate was further cleaned by ion bombardment: the substrate was fixed on the sample holder, and the sample holder speed was set to 4 rpm. When the vacuum degree of the chamber reached 2×10 -5 When the pressure was 0.5 mBar, 30 ccm of Ar was introduced into the chamber, the power of the carbon target was set to 0.05 kW, the power of the titanium target was set to 0.07 kW, and a DC bias of -400 V was applied to bombard and clean the substrate for 1200 s;
[0073] (3) The sample holder continued to rotate at a speed of 4 rpm, the initial power of the carbon target was 0.1 kW, the initial power of the titanium target was 3 kW, the substrate bias was set to -60 V, the argon flow rate was set to 30 sccm, and after sputtering for 840 s with the initial powers of the carbon target and the titanium target to obtain a thin layer of Ti, the power of the titanium target was reduced to 0.05 kW at a rate of 5.9 kW / h; while reducing the power of the titanium target, the power of the carbon target was increased to 3.5 kW at a rate of 6.8 kW / h to obtain an intermediate layer with a thickness of 500 nm.
[0074] (4) The C target power was set to 4.0 kW and the current was 6.7 A; the Ti target power was set to 0 kW and the current was 0; the argon flow rate was set to 25 sccm, the substrate bias was set to -80 V, and the deposition time was 9600 s, thereby obtaining a medical graphite coating with a substrate of single crystal silicon (100) and a medical graphite coating with a substrate of a medical stainless steel substrate (316 steel sheet) (denoted as GLC).
[0075] Example 2
[0076] The only difference from Example 1 is that during deposition in step (4), the Ti target power is 0.10 kW (denoted as Ti-0.10) and the current is 0.34 A.
[0077] The rest is the same as in Example 1.
[0078] Example 3
[0079] The only difference from Example 1 is that during deposition in step (4), the Ti target power is 0.20 kW (denoted as Ti-0.20) and the current is 0.73 A.
[0080] The rest is the same as in Example 1.
[0081] Example 4
[0082] The only difference from Example 1 is that during deposition in step (4), the Ti target power is 0.30 kW (denoted as Ti-0.30) and the current is 1.15 A.
[0083] The rest is the same as in Example 1.
[0084] Example 5
[0085] The only difference from Example 1 is that during deposition in step (4), the Ti target power is 0.40 kW (denoted as Ti-0.40) and the current is 1.52 A.
[0086] The rest is the same as in Example 1.
[0087] The surfaces of the medical graphite coatings with the substrate of single crystal silicon (100) obtained in Examples 1 to 5 were analyzed by SEM. The results are as follows: Figures 1 to 5 shown.
[0088] Depend on Figure 1 It can be seen that the coating cross section is divided into a transition layer and a main layer, and the main layer is composed of a stacked structure.
[0089] Depend on Figures 2 to 5 It can be seen that Figures 2-3 The structure of the middle main layer gradually becomes uniform, and the coating becomes denser; Figure 4 The cross section of the coating shows a flaky structure, and the structure becomes loose, which is mainly due to the effect of the change of Ti doping content on the coating structure; Figure 5 It shows that when the Ti target power is 0.40kW, the structure of the coating becomes dense again.
[0090] The medical graphite-like coatings with a single crystal silicon (100) substrate obtained in Examples 1 to 5 were characterized by Raman spectroscopy. The results are as follows: Figure 6 As shown. Figure 6The obtained Raman spectra were fitted and analyzed, and the results of the ID / IG and G peak positions are shown in Figure 7 shown.
[0091] Depend on Figure 6 It can be seen that the Raman spectrum 2a shows two typical characteristic peaks, corresponding to sp 2 Key and sp 3 G and D peaks of bonds;
[0092] Depend on Figure 7 It can be seen that with the increase of titanium target power, the intensity ratio of D peak to G peak (ID / IG) in the figure first increases and then decreases, and the position of G peak first moves to high wavelength and then to low wavelength. This shows that the sp2 content of the coating deposited at a Ti target power of 0.2kW is the highest, and the sp2 content is the lowest at 0.1kW.
[0093] The microhardness and elastic modulus of the medical graphite coatings obtained in Examples 1 to 5, whose substrates are medical stainless steel substrates, were measured respectively, and fitted into curves as shown in FIG. Figure 8 as shown.
[0094] from Figure 8 It can be seen from the curve that with the increase of Ti target power, the hardness of the coating first increases, then decreases, and then increases again. The microhardness of titanium-doped medical graphite coatings is affected by the ratio of sp2 bonds and sp3 bonds in the coating. Generally speaking, an increase in the content of sp3 hybridized C elements will increase the hardness of the coating. When the Ti target power increases from 0kW to 0.10kW, the hardness of the coating gradually increases, because the value of ID / IG gradually decreases with the increase of Ti target power, which means that the proportion of sp3 hybridized C gradually increases; when the Ti target power increases from 0.10kW to 0.20kW, the hardness of the coating decreases, which is because the loose structure of the coating reduces the hardness of the coating; when the Ti target power increases from 0.20kW to 0.40kW, the value of ID / IG gradually decreases with the increase of Ti target power, which increases the hardness of the coating.
[0095] from Figure 8 It can be seen that the change trend of the elastic modulus of the medical graphite coating is basically consistent with the change trend of the hardness.
[0096] The friction coefficients of the medical graphite coatings obtained in Examples 1 to 5, whose substrates are medical stainless steel substrates, were measured respectively, and fitted into friction coefficient curves as shown in FIG. Fig. 9 As shown in Figure 2, the Raman spectrum of the wear spot after friction is as follows: Fig.10 As shown, Fig.10 The results of ID / IG value and G peak position obtained after fitting analysis are as follows Fig.11 Shown
[0097] Depend on Fig. 9It can be seen that with the increase of Ti target power, the friction coefficient of the coating first decreases and then increases, and the lubrication performance first increases and then decreases: when the Ti target power increases from 0kW to 0.10kW, the friction coefficient of the coating gradually decreases with the increase of Ti target power, and the friction performance becomes better. The friction coefficient of titanium-doped medical graphite coating is mainly affected by the composition of the transfer film formed by the coating during the friction process.
[0098] Depend on Fig.11 It can be seen that the value of ID / IG first increases and then decreases with the increase of Ti target power, which means that the ratio of sp2 / sp3 hybridized carbon first increases and then decreases. The content ratio of sp2 hybridized carbon elements has a greater influence on the friction properties of the coating. An increase in the proportion of sp2 hybridized carbon is beneficial to the improvement of the friction properties of the coating.
[0099] Depend on Fig.12 The wear rate of the medical graphite coating of Examples 1 to 5 whose substrate is a medical stainless steel substrate is shown. The test conditions of the wear rate are: in an atmospheric environment with room temperature and a relative humidity of 40%, a GCr15 ball with a hardness of 6.1 GPa and a diameter of 6 mm is selected as the dual ball, and the motion mode is selected as a reciprocating motion. The normal load, stroke, frequency and number of cycles are 2N, 5mm, 5Hz and 8000 cycles respectively. The wear scar volume after friction is extracted by the three-dimensional morphology imaging technology provided by the equipment, and the wear rate is calculated according to the following formula:
[0100] W=V / (F×S)
[0101] Where W is the wear rate, V is the wear volume, F is the normal load, and S is the sliding distance.
[0102] Depend on Fig.12 It can be seen that with the increase of Ti target power, the wear of the coating first slightly decreases, then increases, and finally decreases. The maximum and minimum wear rates are obtained when the Ti target power is 0.3 kW and 0.1 kW, which are 2.79×10 -6 mm 3 / Nm and 3.18×10 -7 mm 3 / Nm. The wear rate of the Ti-GLC coating increases significantly at high Ti target power, mainly because the generation of TiC hard particles deteriorates the lubrication effect of the coating to a large extent and causes greater wear on the coating, making the wear resistance of the Ti-GLC coating worse.
[0103] The contact angles of the medical graphite coatings obtained in Examples 1 to 5, whose substrates are medical stainless steel substrates, and the simulated body fluids (whose components are shown in Table 2) were measured respectively. The results are as follows: Fig.13 shown.
[0104] Depend on Fig.13It can be seen that the setting of the Ti target power value has a greater impact on the contact angle of the coating. The contact angle increases slightly first, then decreases, and then increases again as the Ti target power increases. The contact angle of titanium-doped medical graphite coating is mainly affected by the surface roughness and internal structure of the coating. Generally speaking, the greater the surface roughness, the smaller the contact angle of the coating and the better the hydrophilicity; when the internal structure of the coating is loose, the contact angle of the coating is smaller.
[0105] The roughness (Ra) of the corresponding titanium-doped medical graphite coating obtained when the Ti target power is 0kW, 0.10kW, 0.20kW, 0.30kW, and 0.40kW are 11.5nm, 8.11nm, 11.4nm, 10.4nm, and 9.07nm, respectively. When the Ti target power increases from 0kW to 0.10kW, the roughness of the coating decreases, thereby increasing the contact angle; when the Ti target power increases from 0.10kW to 0.20kW, the roughness of the coating increases, thereby decreasing the contact angle; when the Ti target power increases from 0.20kW to 0.40kW, the roughness of the coating decreases, thereby increasing the contact angle.
[0106] The cytotoxicity of the titanium-doped medical graphite coatings obtained in Examples 1 to 5 was measured respectively:
[0107] HUVEC cell culture medium (Cellbio, iCell-h110-001b); PBS (Procell, PB180327); trypsin (Biosharp, BL512A); CCK-8 (Invigentech, IV08-100). The HUVEC cells used were human umbilical vein endothelial cells purchased from Shanghai Cellbio Biotechnology.
[0108] The cytotoxicity experiment groups were: control group, medical stainless steel substrate of Example 1, medical graphite coating of medical stainless steel substrate of Examples 1 to 5 (respectively denoted as GLC group, Ti-0.10 group, Ti-0.20 group, Ti-0.30 group, Ti-0.40 group).
[0109] The sample working solution was prepared as follows:
[0110] HUVEC cells were added to the HUVEC cell culture medium and cultured overnight in a 5% CO2, 37°C constant temperature incubator. The medical stainless steel substrate of Example 1 and the medical graphite coating of Examples 1 to 5, which were medical stainless steel substrates, were sterilized by ultraviolet irradiation for 30 minutes. 2 / mL ratio was added to the respective special culture medium, immersed at 37°C for 24 hours, then taken out and filtered for sterilization to obtain the sample solution;
[0111] The special culture medium obtained by overnight culture was stored at 37° C. for 24 hours and then filtered and sterilized to obtain a sample solution of the control group.
[0112] 100 μL / well of the control group sample working solution and the sample working solution prepared from the medical stainless steel substrate of Example 1 and the medical graphite-like coating of the medical stainless steel substrate of Examples 1 to 5 were added respectively; 3 replicate wells were set for each experimental group.
[0113] HUVEC cells in the logarithmic growth phase were taken and 5×10 3 / well was inoculated into a 96-well plate and cultured overnight in a 5% CO2, 37°C constant temperature incubator. According to the above grouping treatment, the culture was continued for 24h, 48h and 72h. After removing the mixture in the well plate, each well was washed three times with PBS buffer, and CCK-8 with 10% of the sample working solution was added at 100μL / well, and cultured in a 5% CO2, 37°C constant temperature incubator for 2h, and finally the absorbance value at 450nm was detected by an enzyme marker.
[0114] The calculation formula of relative cell activity is: relative activity % = (OD value of experimental group - background OD value) / (mean OD value of control group - background OD value) × 100, where the background OD value is the absorbance when only CCK8 reagent is added to the well plate. The calculation results of relative cell activity are shown in Table 1.
[0115] Table 1 Calculation results of relative cell activity of titanium-doped medical graphite coatings obtained in Examples 1 to 5
[0116]
[0117]
[0118] As shown in Table 1, the relative growth rate (RGR) of the obtained coating at 24h, 48h and 72h time points was greater than 80%, and the corresponding cytotoxicity was only level 1, which met the safety toxicity standard.
[0119] From the above examples, it is realized that by controlling the value of Ti target power, titanium-doped medical graphite coatings with different Ti contents are finally obtained. By comparing the effects of different Ti doping on the microstructure, mechanical properties and biological properties of non-magnetron sputtering medical graphite coatings, it is clarified that when the substrate bias is -80V, the C target power is 4.0kW, the argon gas flow rate is 25sccm, and the main layer deposition time is 9600s, the optimal Ti target power of titanium-doped medical graphite coating is 0.20kW. The titanium-doped medical graphite coating prepared under this Ti target power has a dense structure, uniform grain size, optimal hydrophilicity, and a safe toxicity standard.
[0120] In summary, the present invention deposits a titanium-doped medical graphite coating by unbalanced magnetron sputtering technology, and finally obtains a titanium-doped medical graphite coating obtained by unbalanced magnetron sputtering technology by controlling the set value of the Ti target power during the magnetron sputtering process. The obtained titanium-doped medical graphite coating has a dense structure, uniform size, and excellent biological properties.
[0121] Electrochemical testing
[0122] The medical stainless steel sample deposited with the GLC-based coating was used as the working electrode, the platinum mesh was used as the auxiliary electrode, the saturated calomel electrode was used as the reference electrode, and the simulated body fluid (whose composition is shown in Table 2, and the preparation method is as follows: in a volumetric flask filled with 700 ml of deionized water, the compounds in Table 2 were accurately weighed and added in strict order; finally, 1M HCl (i.e., 1M HCl in order 10) and deionized water were added, and the solution was finally fixed to 1L and the pH of the solution was ensured to be 7.40) was used as the corrosion solution. The potentiodynamic polarization curves of the medical graphite-like coatings on the medical stainless steel substrate obtained in Examples 1 to 5 were measured. The results are shown in FIG. Fig.14 shown.
[0123] Table 2 Composition of simulated body fluid
[0124]
[0125]
[0126] Depend on Fig.14 It can be seen that the corrosion potential of the coating after Ti doping has an obvious overall left shift, and the self-corrosion potential increases, indicating that the difficulty of the coating to undergo corrosion reaction increases, and the degree and possibility of its corrosion decreases.
[0127] The corrosion potential and corrosion current density of the medical graphite coatings obtained in Examples 1 to 5 whose substrate is a medical stainless steel substrate were measured in the above-mentioned simulated body fluid. The results are shown in Table 3.
[0128] Table 3 Corrosion potential and corrosion current density of the medical graphite coating on a medical stainless steel substrate obtained in Examples 1 to 5
[0129] Coating samples <![CDATA[E corr (V)]]> <![CDATA[I corr (A / cm 2 )]]> GLC -0.109 <![CDATA[7.755×10 -8 ]]> Ti-0.10 -0.233 <![CDATA[3.495×10 -8 ]]> Ti-0.20 -0.214 <![CDATA[7.163×10 -7 <!-- 8 -->]]> Ti-0.30 -0.242 <![CDATA[3.566×10 -7 ]]> Ti-0.40 -0.292 <![CDATA[7.380×10 -8 ]]>
[0130] As shown in Table 3, the I corr With the initial addition of Ti, the -8 A / cm 2 Down to 3.495×10 -8 A / cm 2Combined with the structural changes of Ti-0.10 coating, it can be seen that the increased density of the coating makes its corrosion resistance better. However, with the increase of Ti content, the corrosion current density of Ti-0.20 coating increases, because the pores on the surface of the coating are conducive to the erosion of the liquid, thereby increasing the corrosion rate. As the Ti content increases to 20.25at.%, the corrosion resistance of the coating gradually increases, and finally slightly better than the pure GLC coating, which is consistent with the change of structural density in SEM and AFM analysis.
[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a medical graphite coating, characterized in that: The steps are: The carbon target and the titanium target are subjected to first unbalanced magnetron sputtering respectively to form a transition layer on the surface of the substrate; the thickness of the transition layer is 500 nm; the substrate is a 316 steel sheet; Performing a second unbalanced magnetron sputtering on the carbon target and the titanium target to form a medical graphite coating on the surface of the transition layer; The thickness of the medical graphite coating is 600-820 nm; Before the first unbalanced magnetron sputtering, the method includes: cleaning the substrate; During the second unbalanced magnetron sputtering, the power of the carbon target is 4 kW and the current is 6.7 A; the power of the titanium target is 0.1 kW and the current is 0.34 A; During the first unbalanced magnetron sputtering, the initial power of the titanium target is 3 kW, the initial power of the carbon target is 0.1 kW, and after sputtering for 840 seconds with the initial power of the titanium target and the initial power of the carbon target, the power of the titanium target is reduced; while the power of the titanium target is reduced, the power of the carbon target is increased; During the first unbalanced magnetron sputtering, the flow rate of the inert gas is 30 sccm.
2. The preparation method according to claim 1, characterized in that: The lowering speed is 3-10 kW / h; the raising speed is 3-10 kW / h; the lowering and raising time is 500-3000 s; The first unbalanced magnetron sputtering ends with the completion of the lowering and the raising.
3. The preparation method according to claim 1 or 2, characterized in that: During the first unbalanced magnetron sputtering: Vacuum degree is less than 2×10 -5 mBar, substrate bias is -60~-80V.
4. The preparation method according to claim 1, characterized in that: During the second unbalanced magnetron sputtering, the flow rate of the inert gas is 25-40 sccm, and the vacuum degree is less than 2×10 -5 mBar, substrate bias is -60~-80V, and deposition time is 5400~10800s.
5. The preparation method according to claim 1, characterized in that: During the first unbalanced magnetron sputtering and the second unbalanced magnetron sputtering, the substrate is in a rotating state, and the rotation speed of the substrate is 2-8 rpm.
6. The preparation method according to claim 1, characterized in that: The cleaning comprises: immersing the substrate in acetone and ethanol successively, performing ultrasound, and then performing ion bombardment.
7. The preparation method according to claim 6, characterized in that: The frequency of the ultrasound is independently 80 to 120 W; the time is independently 10 to 20 min.
8. The preparation method according to claim 6, characterized in that: During the ion bombardment, the rotation speed of the substrate is 2-8 rpm, and the vacuum degree is less than 2×10 -5 mBar, the flow rate of inert gas is 25~40sccm, and the DC bias is -400~-500V.
9. A medical graphite coating prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Amorphous carbon complex coating and preparation method thereof
CN103046001A